Analisis Perencanaan Kebutuhan Guru Berbasis Data Untuk Meningkatkan Kualitas Pendidikan di Sekolah - Galuh Prabowo; Siti Aimah (PT. ALHAFI BERKAH INDONESIA, 2024)
The quality of education in schools is a major concern in efforts to build superior human resources. However, in practice, various obstacles are often encountered that hinder the achievement of these goals. Some teachers may have good academic knowledge but lack effective teaching methods. Therefore, professional training and development programs for teachers must be improved so that they can provide more interesting and effective learning for students. Lack of Accurate Data: Often, data on teacher needs is inaccurate or not well integrated. This causes difficulties in making proper planning. Qualitative research methods are an approach that aims to explore the meaning and deep understanding of a phenomenon. This study uses a case study design which is one form of qualitative research that focuses on in-depth investigation of a particular unit of analysis, such as individuals, groups, organizations, or events. The results of this study indicate that Data serves as an important basis for planning teacher needs effectively. Through data analysis, we can identify specific teacher shortages, uneven distribution of teachers across regions, and gaps in teacher qualifications. Ultimately, data-based planning ensures that every student has access to qualified teachers and high-quality education.